Analysis of The Quality of Inpatient Services From The Patient's Perspective At The Bima Regional General Hospital - Nurwahidah, .; Sastrawan, .; Sulaiman, Lalu; P, Imam Fadhlullah; Kemalahayati, Annisa Dwi; Fahrurrahman, Muhammad (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2024)
The problem raised in this research is the lack of patient satisfaction when being treated at Bima Hospital. According to data on the number of customer complaints regarding the quality of service at Bima Hospital in 2021, there were 1281 complaints, with details including: the number of complaints in inpatient installations was 454 (35.4%), outpatient installations were 295 (23%), Emergency Rooms were 289 (22.6%). %), Radiology was 123 (9.6%), Pharmacy was 45 (3.5%), Nutrition was 44 (3.4%), Others were 35 (2.7%). This is what influences patient satisfaction regarding the services provided by the hospital. Patient satisfaction is a big challenge in providing health services today. This research is a descriptive analytical research using a quantitative approach. With a cross-sectional study research design. This study aims to measure the quality of health services from the patient's perspective while being treated in hospital, analyzing data for descriptive hypothesis testing using the t-test. This research was conducted at Bima Regional Hospital with the research sample consisting of 97 inpatient patients with the sampling technique used was Probability sampling, namely Simple Random Sampling.The results of the research were obtained from the t-Test test of expectations and reality, showed that the Std.Deviation of 9.115 expectations was smaller than the Std.Deviation of 20.265 of reality. So the results of the T-Test test with a p value of 0.000 could be concluded that there was a difference between expectations and the reality that was accepted in review the score given by the patient. And the level of conformity to the results of this research shows that many patients feel that the quality of service provided by the Bima Regional Hospital is very much in line with their expectations.